EVALUATING VOCATIONAL LEARNING MEDIA COMPETENCY: LEARNING OUTCOMES AS A FOUNDATION FOR AGRICULTURAL CONTEXT INTEGRATION - Nurul Fadieny; Islami Fatwa; Septiarini Zuliati (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2025)
This study aims to evaluate student competency outcomes in the Media and ICT for Vocational Learning course within the Mechanical Engineering Vocational Education program, as a basis for developing instructional media integrated with agricultural context. The research employed a descriptive quantitative approach using midterm and final exam scores from the even semester of the 2023/2024 academic year. The results show that students demonstrated strong conceptual understanding, with an average midterm score of 82.25 and final score of 83.00. However, variations in individual achievement indicate the need to strengthen the applicative and contextual aspects of learning. These findings serve as an initial foundation for designing vocational learning media based on simulations, case studies, and real-world agricultural problems, particularly those relevant to the local contexts of North Aceh and Lhokseumawe.